2016
DOI: 10.1002/jcp.25659
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Eph A‐Ephrin A1 System in Endometrial Luminal Epithelial Cells During Early Pregnancy

Abstract: Eph and ephrin regulate diverse biological events such as proliferation, adhesion, migration, and angiogenesis through cell-to-cell interactions. However, little is known of their functional role and mechanisms of action in uterine endometrial cells. In the present study, we demonstrated the effects of the Eph and ephrin on interactions between blastocysts and endometrial luminal epithelial (pLE) cells in the pig that is regarded as an excellent biomedical animal model for research on the peri-implantation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The expressions of Eph A1, A2 and A4 protein in the endometrial stroma underlying the luminal epithelium were the highest on pregnancy Day 18 (Fu, Fu, & Wang, ). In situ hybridization analyses revealed a cell‐specific localization of ephrin A1 mRNAs in the uterine luminal and the glandular epithelia on the pregnant Day 9, 10, 12, 13, 14, 20 and 30) (Lim et al, ). Muc1 proteins (another implantation related gene) were observed in luminal epithelium and stroma by the immunostaining, and the stained Muc1 proteins in the between attachment sites were stronger than that were at the attachment sites on Days 13 and 18 in pigs (Ren, Guan, Fu, & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expressions of Eph A1, A2 and A4 protein in the endometrial stroma underlying the luminal epithelium were the highest on pregnancy Day 18 (Fu, Fu, & Wang, ). In situ hybridization analyses revealed a cell‐specific localization of ephrin A1 mRNAs in the uterine luminal and the glandular epithelia on the pregnant Day 9, 10, 12, 13, 14, 20 and 30) (Lim et al, ). Muc1 proteins (another implantation related gene) were observed in luminal epithelium and stroma by the immunostaining, and the stained Muc1 proteins in the between attachment sites were stronger than that were at the attachment sites on Days 13 and 18 in pigs (Ren, Guan, Fu, & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that ephrin A1 gene could be silenced by shRNAs, and the reduced expressions of ephrin A1 led to the reduction of the capacity of cell migrations and adhesions. In pigs, ephrin A1 enhances interactions between porcine blastocysts and endometrial luminal epithelial cells by activating PI3K and MAPK signal transduction pathways (Lim et al, ). In mice, Haruko Fujii et al () have shown that Eph–ephrin interaction could induce repulsive forces to control cell position and movement (Fujii et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that low Eph‐ephrin A1 expression had advantageous effects on embryo number. Therefore, the results might be attributed to the function of Eph‐ephrin system, which can induce repulsive forces in cell migration and adhesion during embryo implantation in various mammals (Fujii, Fujiwara, Horie, Sato, & Konishi, ; Lim et al., ). LEP protein was also found in the uterus of Yorkshire sows during the pre‐attachment, post‐attachment period (Smolinska, Kaminski, Siawrys, & Przala, ).…”
Section: Discussionmentioning
confidence: 99%
“…The available data have identified some genes that regulate embryo attachment in pigs, and these genes include the following: peroxisome proliferator-activated receptor γ (PPARγ) (Wang, Kong, Hu, Fu, & Wang, 2011), Muc1 , erythropoietinproducing hepatocellular receptor-ligand (Eph-ephrin) system (Fu, Fu, Ren, Chen, & Wang, 2012), obesity gene (or known as leptin or LEP) (Wang, Fu, & Wang, 2014) and leptin receptor (LEPR) (Fu, Li, Li, Fang, & Ren, 2016). Among these genes, Eph-ephrin A1 is an important member of the Eph-ephrin system, which plays an important role in a variety of developmental processes including cell migration, adhesion, vasculogenesis and neuronal plasticity through cell-tocell communication (Kania & Klein, 2016;Lim, Bae, Bazer, & Song, 2016). Eph-ephrin A1 mRNA expression and protein expression are increased in the endometrium and embryo during implantation in humans (Frisen, Holmberg, & Barbacid, 1999;Fujiwara et al, 2002;Red-Horse et al, 2005), mice (Fujii et al, 2006) and embryo attachment in pigs (Fu, Fu, Ren, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%